Antibacterial activity of lactic acid bacteria isolated from Dengke Naniura of Carp (Cyprinus carpio) against diarrhea-causing pathogenic bacteria - Nasri Nasri; Urip Harahap; Jansen Silalahi; Denny Satria (Society for Indonesian Biodiversity, 2021)
Abstract. Nasri, Harahap U, Silalahi J, Satria D. 2021. Antibacterial activity of lactic acid bacteria isolated from Dengke Naniura of Carp (Cyprinus carpio) against diarrhea-causing pathogenic bacteria. Biodiversitas 22: 3098-3104. Diarrhea is the discharge of liquid or watery stools 3 to 4 times a day caused by a bacterial infection. Treatments for diarrhea are probiotics, which have a beneficial effect on the health of the host such as antibacterial. Traditional Batak Toba fermented food, Dengke Naniura, is a source of probiotics. This study aimed to determine the minimum inhibitory concentration, minimum bactericidal concentration, and leakage of DNA and protein from lactic acid bacteria against pathogens. Isolation of LAB was obtained from Dengke Naniura by pour plate method on deMann Rogosa and Sharpe Agar + CaCO3 1%. In this study, Characterization and analysis of bacterial sequencing used Polymerase Chain Reaction. Determination of MIC used the agar diffusion method. The MBC test used the streaking method which was a stroke from the inhibition zone formed. DNA and protein leakage was measured using spectrophotometry UV-VIS (260nm and 280nm). The isolation results obtained were Lactobacillus fermentum, the characterization showed that the bacteria were Gram-positive, bacilli, non-sporing, catalase-negative, and able to ferment sugar. The MIC determination was obtained at a concentration of 10%v/v with a clear zone diameter. Determination of MBC against pathogens was obtained at different concentrations. The results of DNA and protein leakage showed an increased absorption (260nm and 280nm).